Early Exploration of the Moon Ranger to Apollo, Luna to Lunniy Korabl - Lund, Tom (Space Exploration, 2018)
Luna 2, launched by the USSR in 1959, was the first spacecraft from Earth to land on the moon. That first voyage was followed by increasingly capable lunar exploration spacecraft from Russia and the United States. A total of 36 successful lunar exploration missions were conducted from 1959 to the last Apollo manned exploration in 1972 and the final travels of the Lunokhod lunar rover in 1973. Of all the missions, that of Apollo 17 was the pinnacle of manned space exploration. Apollo 17 astronauts traveled 21 miles on the lunar surface in a dune buggy-type vehicle, stopping frequently to explore and gather samples. The spacecraft that enabled lunar exploration were ingenious, and reflected the best efforts of talented people working with the technology of the day. This book showcases the engineering involved in those incredible machines. The spacecraft covered, and their missions, are listed below. From the United States: • Ranger - Photography en route to lunar impact • Lunar Orbiter - Photography of front and back side of moon • Surveyor - Soft landing, photography, and soil analysis • Apollo - Manned exploration. Lunar Rover expanded range From the USSR: • Luna 2 - Photography en route to lunar impact • Luna 3 - Photography of back side of moon on flyby • Luna 9 and 13 - Soft landing, photography, and soil analysis • Luna 10, 11, 12, 14 - Photography from lunar orbit • Luna 16, 20, 24 - Soft landing, return of soil sample to Earth • Lunokhod-1, -2 - Lunar roving vehicle driven from Earth • L1 - Planned manned lunar flyby but only flew unmanned • L3 - Planned manned lunar landing but never flew to moon To tell the story of these spacecraft, Tom Lund draws on over 40 years' work on aircraft and spacecraft systems. He was technical lead for the landing radars for the Surveyor and Apollo spacecraft, and his practical experience is augmented by master's degrees in electrical engineering, physics, and business administration.